A psychological platform for GenAI and human co-piloting in education - Fryer, Luke (Frontline Learning Research, 2025)
GenAI (Generative Artificial Intelligence) will have a growing role within formal education. What should that role be? How do we treat GenAIs as an opportunity to enhance and reenergise teaching and learning? This position paper suggests that answers to these questions should start with our foundational psychological theories about what students need to function and develop well. This position article outlines how psychological needs theory, focusing on students’ basic psychological needs for competence and relatedness might be a path forward. Teacher behavior supporting these psychological needs (i.e., involvement and structure), which have established relationships with learning outcomes, are used as a base for assessing the potential roles of human and AI instructors. A balanced approach that draws on the strengths of each instructor is suggested as a possible way forward for research and practice in this area. Co-piloting the educational ship forward could herald a brighter future for students across educational levels and contexts.